Designing Cross-Cultural Collaborative Online Learning Framework for Online Instructors - Kumi-Yeboah, Alex (Online Learning, 2019)
Online education has now become an integral part of the educational landscape in the United States and around the world, where it serves as the primary source of enrollment growth in higher education. The rising student population in online learning mandates instructors and instructional designers to be aware of the importance of cultural factors that influence students’ learning experiences and academic performance in the online environments. However, few empirical studies have examined instructors’ perspectives on instructional strategies that promote cross-cultural collaboration in online classrooms, specifically, instructional strategies that instructors use to promote educational success of diverse learners in online environments. Drawing on collaborative online learning theory, this study analyzed qualitative interview data and online activities of 40 online instructors from two universities. Results showed the following themes; (a) instructional strategies that facilitate cross-cultural collaborative online learning, (b) challenges of teaching diverse learners in online learning, and (c) designing cross-cultural collaborative online framework for instructors. Findings suggested that most instructors lacked the knowledge and skills in addressing the needs of diverse learners in the online learning environments regarding their ability to recognize students’ cultural differences and incorporate multicultural reading resources in course contents to meet the needs of diverse students. Thus, the need to design a framework will broaden instructors’ understanding and promote cross-cultural collaboration in online teaching to help meet the needs of diverse students in online learning environments. KEYWORDS: Cross-cultural collaborative learning, culturally diverse learners, collaborative learning activities, instructional strategies, Collaboration in online learning